The second summer of the sisterhood - Brashares, Ann (Delacorte, 2003)
With a bit of last summer's sand in the pockets, the Traveling Pants and the Sisterhood that wears them embark on their 16th summer. Bridget: Impulsively sets off for Alabama, wanting to both confront her demons about her family and avoid them all at once